2015
DOI: 10.1111/1471-0528.13777
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal dietary and lifestyle advice for women who are overweight or obese and the effect on fetal growth and adiposity: the LIMIT randomised trial

Abstract: Objective To report the influence of maternal overweight and obesity on fetal growth and adiposity and effects of an antenatal dietary and lifestyle intervention among these women on measures of fetal growth and adiposity as secondary outcomes of the LIMIT Trial. Design Randomised controlled trial. Setting Public maternity hospitals in metropolitan Adelaide, South Australia. Population Pregnant women with a BMI ≥25kg/m2, and singleton gestation between 10+0–20+0 weeks. Methods Women were randomised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
0
44
1
2
Order By: Relevance
“…While this analysis includes data from 845 women and infants (38% of the entire LIMIT cohort), we consider the risk of selection bias to be minimal. The characteristics of the current cohort did not differ significantly from either the characteristics of the Standard Care Group, or the entire LIMIT cohort . Our findings would be enhanced by the inclusion of data from women entering pregnancy with a normal BMI, which will be possible at a later date with the analysis of data from the OPTIMISE randomised trial …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…While this analysis includes data from 845 women and infants (38% of the entire LIMIT cohort), we consider the risk of selection bias to be minimal. The characteristics of the current cohort did not differ significantly from either the characteristics of the Standard Care Group, or the entire LIMIT cohort . Our findings would be enhanced by the inclusion of data from women entering pregnancy with a normal BMI, which will be possible at a later date with the analysis of data from the OPTIMISE randomised trial …”
Section: Discussionmentioning
confidence: 70%
“…For each fetal biometry measure, z ‐scores were calculated using ultrasound growth charts in clinical use . Fetal body composition measurements included mid‐thigh lean mass, mid‐thigh fat mass (MTFM), abdominal fat mass (AFM), and subscapular fat mass (SSFM) using techniques we have previously reported …”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that increased maternal BMI is associated with increased fetal growth as measured by ultrasound fetal biometry . The aim of this secondary analysis from the LIMIT randomised trial was to evaluate, among overweight and obese pregnant women, the degree to which the association between maternal BMI and fetal growth and adiposity was mediated via diagnosed and treated GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal growth and wellbeing at 28 and 36 weeks’ gestation assessed by ultrasound (fetal biometry, estimated weight, liquor volume, umbilical artery Doppler waveform, and adiposity) [34]. …”
Section: Methodsmentioning
confidence: 99%